Hydrogen improves the efficacy of tetrandrine in the treatment of silicosis by inhibiting vascular endothelial mesenchymal transition caused by oxidative stress - Xiao, Kang; Li, Ming; Mu, Yingwen; Sun, Yuxin; Wang, Sirui; Chen, Shangya; Ma, Jiazi; Cao, Mao; Yang, Yong; Shao, Hua; Ding, Xuansheng; Cui, Guanqun; et al. (Frontiers in Bioengineering and Biotechnology, 2026)
ObjectiveSilicosis, a lung disease associated with occupational exposure. Tetrandrine has been approved for the treatment of silicosis in China, but it still cannot be cured. This study aims to investigate the reasons behind the low concentration of tetrandrine (Tet) in lung tissue and propose a treatment plan.MethodsWe first established a silicosis mouse and employed a combination of histological examination, Western blot analysis, immunofluorescence, and single-cell RNA sequencing to clarify the relationship between oxidative stress vascular endothelial mesenchymal transition (EndMT), and Tet concentration in lung tissue.ResultsThe study indicated that there is excessive activation of OS and EndMT in silicosis while concurrently reducing Tet concentration in lung tissue (from 94.8 ± 10.4 ng/mg to 54 ± 6.2 ng/mg). Furthermore, combined inhalation of hydrogen (H2) improved both the severity of silicosis and Tet concentration in lung tissue (from 50 ng/mg to 80 ng/mg). The proposed mechanism suggests that H2 inhibits the release of amyloid precursor protein (APP) in apoptotic alveolar macrophages. Additionally, the interaction between APP and CD74 in vascular endothelial cells was diminished, thereby inhibiting biological processes associated with endothelial mesenchymal transition, alleviating pulmonary vascular stenosis, and enhancing the concentration of therapeutic agents in lung tissue.ConclusionHydrogen can improve the tissue concentration of tetrandrine by anti-OS-induced EndMT.